Biased Opioid Ligands: Revolution or Evolution? - Noble, Florence; Marie, Nicolas (Frontiers in Pain Research, 2021)
Opioid are the most powerful analgesics ever but their use is still limited by deleterious side effects such as tolerance, dependence, and respiratory depression that could eventually lead to a fatal overdose. The opioid crisis, mainly occurring in north America, stimulates research on finding new opioid ligands with reduced side effects. Among them, biased ligands are likely the most promising compounds. We will review some of the latest discovered biased opioid ligands and see if they were able to fulfill these expectations.